Modelling of Epitaxial Growth of Diamond Crystals in High-Carbon Fe—Al Alloys - Mekhed, A.A.; Andryushchenko, V.A. (Наносистеми, наноматеріали, нанотехнології, 2013)
Standard enthalpies of formation of different K-phase unit cells are calculated and compared with formation enthalpy of modified unit cell of K-phase. Spin-polarized calculations are performed to compare electronic structure of carbon atoms in K-phase substrate, diamond, and graphite. An assumption is made on the epitaxial growth of the diamond crystals during the thermobaric treatment of high-carbon Fe—Al alloys.